Strontium-rich injectable hybrid system for bone regeneration - Neves, Nuno (2016)
Current challenges in the development of scaffolds for bone regeneration include the engineering of materials that can withstand normal dynamic physiological mechanical stresses exerted on the bone and provide a matrix capable of supporting cellmigration and tissue ingrowth. The objective of the present workwas to develop and characterize a hybrid polymer–ceramic injectable systemthat consists of an alginatematrix crosslinked in situ in the presence of strontium(Sr), incorporating a ceramic reinforcement in the form of Sr-richmicrospheres. The incorporation of Sr in the microspheres and in the vehicle relies on the growing evidence that Sr has beneficial effects in bone remodeling and in the treatment of osteopenic disorders and osteoporosis. Sr-rich porous hydroxyapatite microspheres with a uniform size and a mean diameter of 555 μmwere prepared, and their compression strength and friability tested. A 3.5% (w/v) ultrapure sodium alginate solution was used as the vehicle and its in situ gelation was promoted by the addition of calcium (Ca) or Sr carbonate and Glucone-δ-lactone. Gelation times varied with temperature and crosslinking agent, being slower for Sr than for Ca, but adequate for injection in both cases. Injectability was evaluated using a device employed in vertebroplasty surgical procedures, coupled to a texture analyzer in compression mode. Compositions with 35%w ofmicrospheres presented the best compromise between injectability and compression strength of the system, the force required to extrude it being lower than 100 N.Micro CT analysis revealed a homogeneous distribution of themicrospheres inside the vehicle, and a mean inter-microspheres space of 220 μm. DMA results showed that elastic behavior of the hybrid is dominant over the viscous one and that the higher storage modulus was obtained for the 3.5%Alg–35%Sr-HAp-Sr formulation.